Analysis of End-User Satisfaction with the E-Learning System as a Learning Support Tool Using the EUCS Method at the Faculty of Tarbiyah and Teacher Training, UIN Raden Fatah Palembang - Supriadi (Institute of Information Technology and Social Science (IITSS), 2025)
The implementation of e-learning began in 2019 using a blended learning approach, and in 2020, the system was updated with new features, including virtual meeting capabilities. To ensure optimal service delivery, universities must maintain system performance by providing satisfaction guarantees for users, assuming that system stability has been achieved. However, there has been no systematic measurement of user satisfaction with the current e-learning system. This study involved 375 active students from the Faculty of Tarbiyah and Teacher Training to measure user satisfaction levels using the End-User Computing Satisfaction (EUCS) method, which includes five variables: content, accuracy, format, ease of use, and timeliness. The results revealed that the hypotheses for content, accuracy, ease of use, and timeliness were accepted, whereas the hypothesis for format was rejected.